Pengelelolaan Fasilitas Laboratorium Komputer di SMA Islam Al Amalul Khair Palembang - Marlina, Leny; Akbar, Ahmad Fauzi; Ibrahim, Ibrahim; Febriyanti, Febriyanti (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to analyze the implementation of computer lab facility procurement, the factors influencing it, and the solutions for the procurement process at SMA Islam Al Amal Khair Palembang. The study was conducted at SMA Islam Al Amalul Khair Palembang using a descriptive qualitative research method. The informants in this study were the school principal and the vice principal in charge of facilities and infrastructure. Data were collected through observations, interviews, and documentation. The data analysis techniques used include data reduction, data presentation, and conclusion drawing, while data validity was ensured through source triangulation and technique triangulation. The research findings indicate that the implementation of computer lab facility procurement at SMA Islam Al Amalul Khair Palembang has been successfully carried out. However, there are several aspects that need further improvement, particularly in the procurement process, to enhance the school's quality and competitiveness with other institutions